PELATIHAN BAHASA INGGRIS BAGI GURU SD N MANYARAN 01 SEMARANG UNTUK MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS - Nurmawati, Nurmawati; Dartani, Maria Yustina Rensi; Setiawan, Agung (LP2M STP Mataram, 2024)
This community service was held with the intention to empower teachers of SD N Manyaran 01 Semarang through English languange training. This service is in the form of training that aims to equip teachers at SD N Manyaran 01 Semarang to be able to have the skills to speak, communicate in English properly and correctly, and this training is intended for all teachers, both English teachers and teachers of other fields of study. Based on observations, participants’English skills vary, some already know how to speak using English, but some do not understand applying the right vocabulary in communicating. This training is carried out in a structured manner within a period of 2 months. Based on the implementation of the training and evaluation of the results, the author concludes that the grammar understanding of SD N Manyaran 01 teachers has increased quite significantly. One of the focuses of the material in this training is the learning of grammar and vocabulary in an integrated manner into speaking activities. The trainees were able to understand grammar more easily and applicatively, so that the English speaking skills of SD N Manyaran 01 Semarang teachers improved significantyly. Participants were more motivated to activity use expressions in English in the school environment. In addition, the confidence and accuracy of the participants’ English vocabulary pronunciation also increased significantly